Cooperative Banking and Regional and Local Development: the Portuguese case - Bento, P.; Crespo, N.; Reto, L. (CIRIEC International - International Symposium, 2023)
Cooperative banking has its idiosyncrasies and is different from the rest. There are several studies that point in this direction, based on the reality of several European countries, including southern Europe, but there is still much to reveal about the Portuguese reality. On the other hand, the consequences of the financial crisis of the previous decade for the banking sector are well known. This study arises precisely in this context, focusing on the following question: did the Portuguese cooperative banking behave identically to the rest of the banks, or did it manage to reach a different level of resilience, which allowed it to face the crisis without massive redundancies and the abandonment of provision of banking services, to inland populations, reinforcing their role in regional and local development? The investigation made use of two types of data: secondary, mainly on banking indicators, both at national and European level, but also on the six Caixas Agrícolas analysed; primary objectives, using exploratory interviews with internal stakeholders, surveys and interviews with internal and external stakeholders. The exploratory interviews aimed to help structure the survey and final validation of the questionnaire. The surveys were made available in digital format (7,397 valid responses), via e-mail, and on paper (3,524 valid responses), through Grupo Crédito Agrícola branches. The data presented throughout this work show that the Group not only withstood the financial crisis better than the rest of the banks, but also continued to play a central role in providing banking services where other banks withdrew, including the public bank.